Efektivitas Penggunaan Media Audio Visual Terhadap Keterampilan Menulis Pengalaman Pribadi Murid Kelas IV SD Negeri Rappojawa No.71 Kecamatan Tallo Kota Makassar - Nur Hizabah; Amal Akbar; Besse Syukroni (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
, This research aims to determine: the effectiveness of audio-visual learning media on Writing Skills, Personal Experiences of Class IV students at Rappojawa State Elementary School. This type of research uses a descriptive quantitative approach with a type of experimental research. Experimental research involving one class, this research includes pretest, treatment and posttest tests. This design was used because this research only involved one class, namely the experimental class which began with a pretest before being given treatment and a posttest after being given treatment. The results of the research show that the use of audio-visual media on writing skills. Personal Experience of Grade IV students at Rappojawa State Elementary School is effective, as can be seen from. The average score of the Indonesian language learning results test in writing Personal Experiences using audio-visual media is 87.20 with a standard deviation of 4.10. From these results it was found that 26 students (100%) had achieved individual completeness and this means that classical completeness had been achieved. achieved, there was effectiveness in student learning outcomes after applying audio-visual learning media because the average value of the normalized N-Gain Test results was 0.70 and was generally in the medium and high categories. From the results of this research, it can be concluded that audio visual media is applied in Indonesian language learning in class IV of Rappojawa State Elementary School, there is significant effectiveness in the use of audio visual media in improving Personal Experience writing skills.